Tatalaksana Ventilasi Pada Pasien Coronavirus Disease 2019 (COVID-19) - Tungki Pratama Umar (Bahasa Indonesia, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) is a respiratory infection that has become a global pandemic. Approximately 5% of all sufferers of this disease require an intensive care unit, with Acute Respiratory Distress Syndrome (ARDS) as one of the main complications with a mortality ratio reaching 94%. COVID-19 which disrupts the respiratory system requires adequate management, especially in ventilation or oxygenation to reduce the risk of multi-organ damage. The author discusses this topic in this literature review. Results: Ventilation management in COVID-19 patients must adhere to the principles of Safe (for staff and patients), Accurate (preventing unusual techniques), and Swift (fast). Airway management in COVID-19 patients has a very high risk because of the large opportunity for aerosolization to occur. Providing ventilation (oxygenation) to patients with COVID-19 has many options, ranging from the nasal cannula, face mask, rebreathing masks, Venturi Mask, Non-rebreathing Mask (NRM), High Flow Nasal Cannula, Non-Invasive Ventilation (NIV), to intubation with mechanical ventilation. Regarding intubation, until now there is no specific protocol, especially regarding disagreements about early or late intubation. Conclusion: The choice of oxygen administration technique, as well as the decision to intubate, largely depended on the discretion of the anesthetist who is present and assesses it according to the individual needs and clinical status of the patient.